Associação entre resiliência e autopercepção de saúde em adultos de São Leopoldo, Rio Grande do Sul, Brasil - Santos, Desirée dos (Universidade do Vale do Rio dos Sinos, 2010)
Self-perception of health is one of the indicators recommended by the World Health Organization to assess the health of populations (Theme Filha, Szwarcwald and Souza Junior, 2008), it measures the individual's health status in a global way and has acquired importance for research. epidemiological data (Alves and Rodrigues, 2005). A concept for health must be linked to the way in which society is organized, without disregarding individual particularities. It is therefore necessary to try to directly understand health, as it is perceived and felt by people and what are the determinants (Brodersen, 1997). Increasingly used in epidemiological research, self-perception of health is strongly associated with the actual or objective health status (Dachs, 2002; Santos et al., 2007).
Keywords: Saúde em adultos; Resiliência e autopercepção de saúde; São Leopoldo; Health in adults; Resilience and self-perception of health; ACCNPQ::Ciências da Saúde::Saúde Coletiva